Audit Findings, Follow-Up, and Financial Reporting Quality Fail to Reduce Corruption - Desriani Hadi; Einde Evana; Fajar Gustiawaty Dewi (Academia Open, 2026)
General Background Corruption in public sector institutions remains a persistent governance challenge in Indonesia despite extensive external audit mechanisms. Specific Background The Supreme Audit Agency conducts audits of ministries and institutions, producing audit findings and follow-up recommendations intended to strengthen accountability and transparency through financial reporting. Knowledge Gap Prior empirical studies report inconsistent evidence on whether audit findings and follow-up actions are associated with corruption, particularly when financial reporting quality is positioned as a mediating mechanism. Aims This study examines the direct and indirect relationships between audit findings, follow-up on audit results, and corruption, with financial reporting quality as an intervening variable, within the framework of agency theory. Results Using panel data from 132 ministry and institutional observations during 2021–2023, the findings show that audit findings are negatively associated with financial reporting quality, while audit follow-up is positively associated with financial reporting quality. However, audit findings, audit follow-up, and financial reporting quality show no significant direct relationship with corruption, and financial reporting quality does not mediate these relationships. Novelty This study provides rare empirical evidence that financial reporting quality does not transmit the role of audit mechanisms into corruption control within Indonesian ministries and institutions. Implications The results indicate that audit processes and reporting improvements primarily function as administrative accountability tools and are insufficient as standalone instruments for addressing corruption in the public sector. Highlights: Audit observations are associated with lower standards of governmental financial statements. Recommendation completion is linked to improved compliance with accounting standards. Reporting mechanisms do not explain variations in misconduct cases across institutions. Keywords: Audit Findings, Follow-Up, Quality of Financial Statements